A NEW SPECIES OF ONOSMA (BORAGINACEAE–LITHOSPERMEAE) FROM SOUTHERN TURKEY - RIEDL, H.; BINZET, R.; ORCAN, N. (Edinburgh Journal of Botany, 2005)
A new species of Onosma (Boraginaceae), O. mersinana, in sect. Asterotricha, is described from southern Turkey, and its affinities discussed.